Hydromorphone ameliorates postoperative pain and depressive disorder in women receiving cesarean section under spinal anesthesia - Ouyang, Rongyi; Jiang, Jinming; Li, Wenqiang; He, Fu; Yang, Libin; Kou, Xianbing; Dai, Junchao; Xu, Mingliang; Liu, Yulin; Zhan, Jian (Frontiers in Medicine, 2025)
BackgroundPain and depressive mood disorders during cesarean sections negatively impact both mothers and infants. Studies have shown that hydromorphone has positive effects on both pain management and depressive mood disorders. This study examines how hydromorphone influences postoperative pain and depressive disorders in parturients undergoing cesarean sections under spinal anesthesia.MethodsThis single-center, controlled, randomized trial involved 130 patients. Parturients in the intervention (H) group received patient-controlled intravenous analgesia (PCIA) with hydromorphone combined with sufentanil, while those in the control (S) group received sufentanil alone. All cesarean sections were performed under spinal anesthesia. Postoperative pain scores at rest and during movement were assessed using the Visual Analog Scale (VAS) at 4 h (T0), 8 h (T1), 12 h (T2), 24 h (T3), and 48 h (T4) postoperatively. The Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) were utilized to measure depressive and anxiety disorders at 3 days and 6 weeks postoperatively. Adverse reactions were also recorded.ResultsThe H group had significantly lower resting VAS scores at all postoperative time points (p = 0.008) and significantly lower movement VAS scores (p < 0.001) compared to the S group. At 3 days postoperatively, BDI scores showed no statistically meaningful variations (p = 0.057) or BAI scores (p = 0.444) between the two group. However, at 6 weeks postoperatively, the H group had significantly lower BDI scores (p = 0.001) and BAI scores (p = 0.012). No statistically significant differences in operative time were observed between the groups. (p = 0.086), time to first ambulation (p = 0.092), sleep quality scores (p = 0.132), or adverse reactions, including chills (p > 0.999), pruritus (p = 0.109), nausea and vomiting (p = 0.718), respiratory depression (p = 0.619), or dizziness (p = 0.619).ConclusionThe synergistic use of hydromorphone and sufentanil in PCIA provides superior analgesia for postoperative pain and decreases postoperative depression and anxiety scores in parturients undergoing cesarean sections.